2013
DOI: 10.1161/circimaging.112.000259
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Ischemia and Outcomes in Outpatients With Diabetes Mellitus Referred for Single-Photon Emission Computed Tomography Myocardial Perfusion Imaging

Abstract: Background The prevalence of ischemia and its prediction of events are unclear in outpatient diabetic patients in the modern era of intensive medical management. We sought to identify the prevalence of ischemia, subsequent cardiac events, and impact of gender, stress type, and symptom status on these findings in a cohort of outpatient, stable diabetic patients referred for SPECT myocardial perfusion imaging (MPI). Methods and Results The study cohort included 575 consecutive diabetic outpatients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 43 publications
2
24
0
2
Order By: Relevance
“…Remarkably, the prevalence of ischemia and its prediction of events are unclear in outpatients with diabetes mellitus in the modern era of intensive medical management. Bourque et al 28 recently sought to identify the prevalence of ischemia, subsequent cardiac events, and impact of sex, stress type, and symptom status on these findings in a cohort of stable outpatients with diabetes mellitus referred for MPS. Known CAD was present in 40.3% of subjects and 29% were asymptomatic at the time of stress testing.…”
Section: Prognostic Value Of Exercise Level In Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the prevalence of ischemia and its prediction of events are unclear in outpatients with diabetes mellitus in the modern era of intensive medical management. Bourque et al 28 recently sought to identify the prevalence of ischemia, subsequent cardiac events, and impact of sex, stress type, and symptom status on these findings in a cohort of stable outpatients with diabetes mellitus referred for MPS. Known CAD was present in 40.3% of subjects and 29% were asymptomatic at the time of stress testing.…”
Section: Prognostic Value Of Exercise Level In Diabetic Patientsmentioning
confidence: 99%
“…Noteworthy, in this study nearly one third of patients with events had a normal MPS, indicating a need for improved risk stratification. 28 Thus, the relationship among METS, stress-induced ischemia, and prognosis in diabetic subjects remains unclear. In another recent study, Duvall et al 29 showed that a provisional injection protocol defined as age \65, normal rest ECG, no history of CAD, and high level exercise (C10 METS) with a negative ECG response and no symptoms has a very low 5-year all-cause mortality and low yield of MPS.…”
Section: Prognostic Value Of Exercise Level In Diabetic Patientsmentioning
confidence: 99%
“…Alrededor de 1/3 de los pacientes con eventos tenían SPECT normal, lo que para los autores indica que se requiere mejorar la estratificación previo al estudio con SPECT. 17 Esto último, diferencia ese trabajo del nuestro en el que no se había solicitado el examen como parte de su manejo habitual. De acuerdo al estudio DIAD en DM asintomáticos cardíacos, el uso de estudios con provocación de isquemia no se aconseja entre otras causas por la baja capacidad de detección de la prueba, número de eventos relativamente bajo que no parecen afectar la evolución y además su alto costo.…”
Section: Materials Y Métodosunclassified
“…It has been observed that the prevalence of high risk CAD and ischemia on stress imaging in diabetic patients may be decreasing, presumably because of both effective primary and secondary prevention (11). This correlates well with the overall decrease in significant inducible ischemia seen in patients referred for stress SPECT imaging (12).…”
mentioning
confidence: 99%
“…Bourque et al (11) prospectively evaluated 575 consecutive diabetic patients (29% asymptomatic) who underwent stress SPECT myocardial perfusion imaging. Ischemia of ≥10% of the left ventricle was seen in only 5.0% of the patients imaged.…”
mentioning
confidence: 99%